Negotiorum Gestio: the Element of Emergency in the Doctrine of Informed Consent - Lytvynenko, Anatoliy A.; Machovenko, Jevgenij; Jurkeviča, Tatjana I. (Teisė, 2024)
The rule of an obligatory consent of a patient for a medical procedure has its exceptions, one of the most cited of which is a condition of emergency, under which the physician is not under the obligation to seek for the patient’s consent, but to provide the treatment, which is strictly necessary upon the physician’s best judgment, and will not be liable for an unconsented medical procedure in such case. In many legal cases on the issues regarding consent to medical procedures, the courts expressed the view that consent to medical treatment is a prerequisite to its legitimacy, unless an emergency occurs and hence it would be impossible to obtain the patient’s consent. In some early 20th century cases, the emergency exception was also invoked when patients were unconscious under anesthesia, and the physicians found a serious health impairment during the operation, which differed from the purpose of the previously agreed operation. In this article, the authors have analyzed the exception of emergency within the Roman law concept negotiorum gestio, focusing on the details of the legal cases, in which an emergency was invoked, being either alleged, or proved. The authors have also examined the historical legal foundations of the right of physicians to carry out medical treatment (which in some cases includes surgeries), and found that the legal doctrine has no uniform answer to this question, whereas various legal doctrines, including customary law, were historically used to describe these legal foundations.
Keywords: medical law; physician’s rights; patient’s rights; informed patient’s consent; emergency medical care; medical malpractice; negotiorum gestio